2019
DOI: 10.3390/molecules24091723
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Antiviral Activity of Mizoribine Against Foot-And-Mouth Disease Virus

Abstract: Foot-and-mouth disease (FMD) is a highly contagious viral disease of cloven-hoofed animals, which has significant economic consequences in affected countries. As the currently available vaccines against FMD provide no protection until 4–7 days post-vaccination, the only alternative method to control the spread of FMD virus (FMDV) during outbreaks is the application of antiviral agents. Hence, it is important to identify effective antiviral agents against FMDV infection. In this study, we found that mizoribine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This plant has also been tested against papillomavirus type 1 (PV-1) 52 and herpes simplex virus (HSV) 53 using polysaccharides. In addition, aqueous extracts of this herbal medicine have been shown to be effective against foot-and-mouth disease 24 , 54 . Furthermore, flavonoids from this species of Meliaceae inhibited the viral activity of several influenza strains (H 1 N 1 , H 1 N 2 , H 2 N 2 , H 2 N 3 , H 5 N 1 , H 7 N 2 , H 7 N 3 , H 7 N 7 and H 9 N 2 ) 55 .…”
Section: Discussionmentioning
confidence: 99%
“…This plant has also been tested against papillomavirus type 1 (PV-1) 52 and herpes simplex virus (HSV) 53 using polysaccharides. In addition, aqueous extracts of this herbal medicine have been shown to be effective against foot-and-mouth disease 24 , 54 . Furthermore, flavonoids from this species of Meliaceae inhibited the viral activity of several influenza strains (H 1 N 1 , H 1 N 2 , H 2 N 2 , H 2 N 3 , H 5 N 1 , H 7 N 2 , H 7 N 3 , H 7 N 7 and H 9 N 2 ) 55 .…”
Section: Discussionmentioning
confidence: 99%
“…intracellular GTP pools [12,13,18]. Therefore, the mechanism of MZR against BKPyV may be also involve inhibition of IMPDH, further in Vitro and in Vivo experiments are needed.…”
Section: Discussionmentioning
confidence: 99%
“…During the conversion from MMF to MZR, the lower risk of virus infection might be associated with the reduced intensity of immunosuppression, which facilitates the immune system to kill the virus. Significantly, in vitro and in vivo studies showed that MZR could inhibit the replication of CMV, hepatitis C virus, and foot-and-mouth disease virus [11][12][13]. Previous studies have also suggested conversion from MMF to MZR correlated with lower BKPyV viruria/viremia [14,15].…”
mentioning
confidence: 97%
“…cDNAs were synthesized using a PrimeScript™ RT reagent kit containing gDNA Eraser with random hexamers. The synthesized cDNAs were subjected to Q-PCR analysis using specific primers as described previously (Li et al, 2019). Q-PCR was performed in triplicate on an Agilent Technologies Stratagene Mx3005 P instrument (Agilent, USA) using SYBR Premix Ex Taq™ II (Tli RNaseH Plus) in a 25 μL reaction mixture.…”
Section: Rna Extraction and Q-pcr Analysismentioning
confidence: 99%